Are Daphnia similis Playing a Significant Role in Microplastic Biofragmentation? - Rani-Borges, Bárbara [UNESP]; Pompêo, Marcelo; Queiroz, Lucas Gonçalves (Springer Nature, 2023)
Environmental plastic contamination is a global problem, which is driven by the growing demand for plastics. Over time, plastics undergo fragmentation processes and become so-called microplastics, which have been shown to be a threat to the various environments where their presence occurs. The most accepted hypothesis is that, like macroplastics, microplastics have fragmented into smaller and smaller particles, with sub-micrometer sizes. However, little is known about fragmentation rates and which are the most determining factors in this process. The main objective of the present study was to investigate the biofragmentation capacity of microplastics by Daphnia similis, a microcrustacean from inland waters. The organisms were exposed to polystyrene spheres (PS; 24 µm), under two concentrations: 135 and 1350 items/50 mL, for a period of 6 days. The rate of biofragmentation was obtained by analyzing the size of the particles over time (48, 96, and 144 h); ingestion and survival rates were also investigated. At the end of the exposure, the microspheres had their size reduced by 32.8%. From the first 48 h, the organisms ingested particles, and the rate of ingestion was dose dependent. Mortality was shown to increase in the treatment of higher concentration. The results demonstrate the ability of this microcrustacean to induce the reduction of the dimensions of microplastics, evidencing a fragmentation pathway previously neglected.
Keywords: Crustaceans; Fragmentation; Freshwater invertebrates; Nile Red; Polystyrene PS